- PEMBERDAYAAN LITERASI AL-QUR’AN INKLUSIF BAGI KOMUNITAS DIFABEL KAWAN NETRA SURABAYA MELALUI STRATEGI PARTICIPATORY ACTION RESEARCH (PAR) - alindah lutfiyah (LPPI UMN AL WASHLIYAH, 2025)
This community empowerment program on Qur’anic literacy for visually impaired learners in Surabaya was implemented using a Participatory Action Research (PAR) approach to ensure an inclusive, collaborative, and needs-based learning process. The findings indicate that improving technical skills in reading the Qur’an in braille alone was insufficient to meet participants’ comprehensive literacy needs, highlighting the importance of understanding Qur’anic meaning. Through braille reading sessions, tajwīd discussions, and makhraj practice, participants developed an awareness of the necessity of access to tafsīr to enrich their spiritual experience. The tafsīr sessions of Surah Al-Kahf, conducted in a dialogic and adaptive manner, encouraged participants to interpret the verses, ask critical questions, and relate Qur’anic messages to their lived experiences. This process demonstrates that Qur’anic literacy is multidimensional and that PAR effectively fosters an empowering and egalitarian learning environment. Overall, the program not only enhanced technical reading abilities but also cultivated critical awareness, spiritual independence, and sustained motivation for learning, making it a potential model for inclusive Qur’anic literacy initiatives among visually impaired communities elsewhere.